Socrates in Quarantine - Mladenova, Viki (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): Viki Mladenova Title (English): Socrates in Quarantine Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 154-157 Page Count: 4 Citation (English): Viki Mladenova, “Socrates in Quarantine,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 154-157.